A method for preparing an asymmetric porous TPU / Ag@K2Ti4O9 conductive film
Through a non-solvent phase separation method, silver-coated tetratitanate whiskers combined with thermoplastic polyurethane (TPU) solution were used to prepare a simplified process and asymmetric porous conductive film, which solved the complex preparation process in the prior art and The problem of difficult material recycling has achieved efficient and environmentally friendly conductive film preparation.
Patent Information
- Application Number
- CN202210937586.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-05
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2042-08-05
AI Technical Summary
In the prior art, the preparation process of porous multi-layer composite conductive films is complex, and the film materials are difficult to recycle and reuse, and the precious metal nanomaterials used are costly, which limits its market application.
By a non-solvent phase separation method, silver-coated potassium tetratitanate whiskers were added to a thermoplastic polyurethane (TPU) solution dissolved in DMF to prepare a slurry, and asymmetry was prepared by one-step method Porous conductive film.
A simplified process is achieved, complex processing and interface bonding are avoided, and a porous conductive film with an asymmetric structure is prepared. The skin layer has hydrophobic and protective functions, the bottom layer has good conductivity, and the film can be recycled and utilized for maximum Reduce environmental pollution.
Smart Images

Figure CN115148395B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of asymmetric porous conductive film preparation, and in particular to a method for solidifying Ag-coated K2Ti4O9 whiskers and polymer mixed slurry (TPU / Ag@K2Ti4O9) into an asymmetric porous conductive film by a special non-solvent induced phase separation method. Background Art
[0002] At present, the use of microsensors has gradually developed from laboratories to real-world applications such as health monitoring and human-computer interaction, which has put forward new requirements for these sensors. Among them, thin-film flexible conductive materials with sensing properties are the most mainstream choice. There are many kinds of thin films with sensing properties, most of which are composite materials that fully mix the conductive reinforcement phase with the matrix that maintains physical properties to make it a composite film with a certain elasticity. As the bearer of the conductive function, many scholars have done a lot of work on the selection of such materials. Materials using carbon black, carbon nanotubes, conductive polymers, nanosilver particles, and silver nanowires have achieved good tensile properties. However, they have more or less some problems, such as the high cost of conductive polymers and silver nanowires, easy agglomeration if improperly handled, easy oxidation of conductive polymers after being placed for a long time, poor long-term storage stability, and poor dispersion of carbon nanotubes and silver nanoparticles. In order to improve these defects, researchers will fine-tune the morphology of the material, such as preparing composite fiber to form a mesh structure through spinning and then making it into a membrane, or using a loading method such as loading graphene on a copper mesh, etching the copper mesh and loading it on a polymer to make a high-performance stretch sensing film, or even directly using 3D printing to obtain a microstructure to give the material stretch sensing performance. However, these fine-tuning processes often require complex processes and composite materials are difficult to recycle.
[0003] So far, there have been many reports on conductive films. By searching relevant literature in the past two years: China Patent Publication No.: CN113889295A, publication date is January 4, 2022, named a conductive film and its manufacturing method, the patent specification discloses that the conductive film includes a four-layer structure: from bottom to top, a substrate layer, a thermoplastic polyurethane composite layer, a conductive layer and a thermoplastic polyurethane surface layer. The thermoplastic polyurethane composite layer includes a thermoplastic polyurethane heat-resistant layer and a thermoplastic polyurethane hot-melt layer, the thermoplastic polyurethane heat-resistant layer is arranged on the thermoplastic polyurethane hot-melt layer, and the thermoplastic polyurethane hot-melt layer is arranged on the substrate layer. The conductive layer includes a conductive circuit, and the conductive circuit is arranged on the thermoplastic polyurethane heat-resistant layer. The thermoplastic polyurethane surface layer is arranged on the conductive layer. Utilizing the design of the thermoplastic polyurethane composite layer, the conductive layer will not directly contact the substrate layer. Therefore, when the substrate layer is pulled, the conductive circuit of the conductive layer can be prevented from being broken, which can improve the service life of the product. The main feature of this patent specification is that a multilayer structure is obtained by processing, rather than a solvent-induced phase separation method to directly prepare an asymmetric multilayer conductive film. At the same time, a conductive circuit is used on a conductive substrate. The Chinese patent publication number is: CN113871054A, and the publication date is December 31, 2021. The name is a flexible transparent conductive film and a preparation method thereof. The flexible transparent conductive film provided by the patent is composed of polyimide (PI) and silver nanowires (Ag NWs). Ag NWs are embedded in PI and modified by a self-assembled layer of pentafluorobenzenethiophenol (PFT) to obtain a flexible transparent conductive film with high conductivity, high transmittance, high adhesion, and surface work function matching. There is another Chinese patent publication number: CN113838598A, the publication date is December 24, 2021, and the name is an antioxidant low-resistance transparent conductive film. The conductive film body includes a base film layer, a silver film layer and a protective layer. The silver film layer is arranged on the base film layer, and the protective layer is arranged on the silver film layer. This also requires a complex processing method to enable the film to obtain good properties such as low resistance, high transparency, anti-fingerprint oxidation, and weather resistance. The Chinese patent publication number is: CN113381122A, the publication date is September 10, 2021, and the name is a method for preparing a porous meta-aramid membrane by a non-solvent-induced phase separation method. It is also a film with special properties prepared by a non-solvent-induced phase separation process. The inventor adjusts the composition of the casting liquid, the composition of the coagulation bath and the molding conditions, and uses a step coagulation bath to prepare a porous meta-aramid membrane with excellent epidermal pore structure and internal pore structure.It has the characteristics of simple preparation process, short molding time, easy adjustment of preparation process, low energy consumption, and suitability for large-scale industrial production; although the published specification also uses non-solvent induced phase separation to prepare thin films with special properties, it controls the coagulation bath to achieve the non-solvent induced phase separation process achieved by liquid water and solutes in water under the conventional definition, thereby preparing porous films with special properties. By comparing the existing public literature, most of the prior art uses post-processing to composite multilayer films onto the same film layer, or uses a variety of complex materials to prepare composite films. All have the disadvantages of complex processing and difficulty in recycling after damage. In addition, in the disclosed technology, the widely used silver nanowires and MXene are also relatively expensive, which limits their widespread application in the market. Summary of the invention
[0004] The present invention aims at solving the problems in the prior art that the preparation process of porous multi-layer composite conductive films is complicated and the film materials are difficult to recycle and reuse. The present invention provides a method for preparing an asymmetric porous conductive film by a unique non-solvent induced phase separation method. Through a one-dimensional material anchoring mechanism, core-shell Ag@K2Ti4O9 whiskers are used as reinforcing phases and added to a polyurethane (TPU) solution dissolved in DMF to prepare a slurry. The slurry has the dual functions of anchoring the polyurethane (TPU) slurry during the film forming process and forming a conductive network after forming, so that an asymmetric porous conductive film is prepared in one step.
[0005] The object of the present invention is achieved by a method for preparing an asymmetric porous TPU / Ag@K2Ti4O9 conductive film, characterized in that it comprises the following steps:
[0006] a) Thermoplastic polyurethane (TPU) and N, N-dimethylformamide (DMF) are mixed to prepare a mixed solution with a mass concentration of 15-25%, and a uniformly dispersed slurry A is obtained after the mixture is completely dissolved; in this step, the mass concentration range of TPU is reasonably optimized and controlled. If the mass concentration of TPU is too low, the viscosity of the system will decrease, the anchoring effect of the silver-coated potassium tetratitanate conductive whiskers on TPU will be weakened, and an uneven film will be generated. If the mass concentration of TPU is too high, the system will lose its fluid properties like whipped cream and cannot automatically become flat in the container;
[0007] b) Add 15-25% of the total mass of slurry A in step a) to slurry A with Ag@K2Ti4O9 conductive whiskers, stir for 20-40 min under dry conditions, and then let stand for 10-20 min under dry conditions to obtain a uniformly dispersed conductive slurry B; in this step, first control the proportion of Ag@K2Ti4O9 conductive whiskers added to slurry A to the total mass of slurry A. If too much is added, the mechanical properties of the conductive film will be reduced, making it easy to break. If too little is added, the electrical properties of the conductive film will be reduced, making its resistance larger. At the same time, the amount added will also affect the special non-solvent induced phase separation process; c) Pre-cured film: Evenly spread the conductive slurry B in step b) on the surface of the glass plate, let it stand for defoaming in a dry environment for 10-20 min, and then transfer it to a temperature of 20-30 ° C and a relative humidity of 40-60% RH for 1-3 hours. h, and the pre-cured product C is obtained; in this step, a reasonable defoaming time can ensure that there are no bubbles on the surface of the finished product. If the time is too long, the film will dry and become an airtight and non-porous film; the temperature should be between 0-30 degrees Celsius. If the temperature is too high, the anchoring effect of TPU on the conductive whiskers will disappear, and an asymmetric structure will not be formed, and a symmetrical conductive film will be generated; the humidity cannot be too low, otherwise the film will dry and become thin. This process will last for more than 1 hour to complete the non-solvent-induced phase separation process;
[0008] d) The pre-cured product C in step c) is immersed in water for 1-3 hours together with the glass plate to completely cure it, and the film is peeled off to obtain a cured film D. In this step, in order to completely remove the DMF in the conductive film, the pre-cured product C is immersed in water together with the glass plate or culture dish for 1-3 hours to completely cure it, and the film is peeled off to obtain a cured film D. The reason for pre-curing together with the glass plate is that the physical strength of the pre-cured product C is similar to that of chewed gum, which can withstand the impact of water but has not yet been fully formed, and pulling it will damage it;
[0009] e) The film cured in step d) is naturally dried at room temperature to obtain a porous PU / Ag@K2Ti4O9 conductive film. In this step, natural drying is selected instead of drying or blowing, because although step d has almost completely removed the DMF in the film, there is still a very small amount of DMF in the chain segment of TPU, which has no effect on the film at low temperatures, but the DMF in the chain segment will lower the melting point of TPU, and will melt it at high temperatures, thereby destroying its structure. However, after the film is naturally dried for a few days and the DMF is completely removed, the film can withstand high temperatures below 140 degrees Celsius.
[0010] The preparation method of the asymmetric porous TPU / Ag@K2Ti4O9 conductive film of the present invention innovatively provides a technology for preparing an asymmetric porous conductive film that is different from the existing technologies for preparing conductive films. The core of the technology is to use a special non-solvent-induced phase separation method to form the film. This special non-solvent-induced phase separation method is defined as: through a one-dimensional material anchoring mechanism, core-shell Ag@K2Ti4O9 whiskers are used as reinforcing phases, which simultaneously play the dual role of anchoring the polyurethane (TPU) slurry during the molding process and forming a conductive network after molding. Before molding, it is added to a polyurethane (TPU) solution dissolved in DMF to form a slurry. Compared with the common non-solvent phase separation method (i.e., the solution of TPU dissolved in DMF is flattened and directly immersed in water to obtain a porous TPU film), the special non-solvent phase separation method used in the present invention is special in that: 1. Silver-coated potassium tetratitanate whiskers are used as reinforcing phases and directly mixed with TPU solution. By controlling the content of silver-coated potassium tetratitanate whiskers, TPU, and DMF components, the state of the uniformly dispersed conductive paste B in step b is just controlled to be viscous, and when water molecules enter, TPU is immediately precipitated and it can remain in the best state of fluid for film formation; Due to the affinity between whiskers and TPU, the precipitated TPU molecular chains have an "anchoring effect" on whiskers, fixing the whisker structure. With the entry of water molecules, TPU in the system expands as DMF absorbs water and expands. The whiskers cannot expand after being fixed by the anchoring effect. It can be understood that before molding, these whiskers are loose powdery "one-dimensional materials". After the initial molding, once water molecules enter, the original TPU slurry is both viscous and fluid. Due to the "anchoring effect", these whiskers become a whole, that is, a "three-dimensional material", and are no longer a powdery "one-dimensional material" that can flow freely. This makes part of the TPU have to pass through the whisker network to form a hydrophobic epidermis (protective layer) on the surface. Its superiority lies in the fact that it does not require special processing, and the asymmetric structure is formed in one step. The conductive film with a composite structure of epidermis, porous conductive layer and substrate layer avoids complex process and interface bonding. 2. Compared with the ordinary non-solvent-induced phase separation process, it is directly soaked in water, and the pre-curing process of standing at a higher humidity for 1-3 hours is added. Using the water absorption of DMF, water vapor in the air enters the system to cause non-solvent-induced phase separation. Compared with liquid water, the phase separation is relatively slow. After the film is basically pre-cured to obtain the pre-cured product C, which has a certain physical strength, it is then immersed in water to completely cure it; the advantage is that it avoids the water flow damaging the uncured fragile film during direct immersion in water.In addition, the surface layer of the conductive film with an asymmetric porous structure prepared by the present invention is a fluffy porous structure with a porous conductive layer inside it, so its surface is not conductive and will not be disturbed by charged objects when detecting pressure. At the same time, due to its porous structure, extremely slight pressure will have a more obvious effect on its resistance. At the same time, due to the excellent conductivity of the bottom, the output of its resistance signal is extremely convenient. It only needs to connect electrodes at the bottom to form a pressure-sensitive sensor.
[0011] Furthermore, the mass ratio of TPU to Ag@K2Ti4O9 conductive whiskers is 1:1.
[0012] Furthermore, in step b), the conductive whisker is a core-shell Ag@K2Ti4O9, and the mass ratio of the surface-coated silver element in the conductive whisker is 60-90%.
[0013] Furthermore, in order to form a film of a certain thickness, in step c), the conductive paste B is applied on the glass plate at a thickness of 0.1 to 0.3 g / cm 2 .
[0014] Furthermore, Ag@K2Ti4O9 conductive whiskers are prepared by the following method: potassium tetratitanate whiskers are baked at 100°C for 30 to 60 minutes, and then glucose and distilled water are added at room temperature, wherein the mass ratio of potassium tetratitanate, glucose and distilled water is 1:6 to 10:3 to 5. After mixing, they are ultrasonically treated at room temperature for 10 to 20 minutes until the glucose is completely dissolved and the whiskers are completely dispersed. Then, silver ammonia solution is added, and the mixture is reacted in an oscillator at 40 to 50°C at a speed of 200 times / second for 24 to 30 hours. Then, the mixture is filtered, washed, and dried to obtain Ag@K2Ti4O9 conductive whiskers.
[0015] Furthermore, the aspect ratio of the potassium tetratitanate whisker is 10-15.
[0016] In the preparation method of the asymmetric porous conductive film provided by the present invention: by using a special non-solvent phase separation method, a porous conductive film with an asymmetric structure is obtained in one step, and its epidermis has hydrophobic and protective functions, and the epidermis is non-conductive, and its bottom layer has good conductivity. Through electron microscopy, it can be found that its surface and cross-section have a special asymmetric porous structure. At the same time, the matrix of this porous composite structure is a thermoplastic polyurethane (TPU) that can be repeatedly dissolved in DMF, and the reinforcing phase is a silver-coated potassium titanate conductive whisker with a length of about 20 microns and a diameter of about 1 micron. When the film is damaged, it can be dissolved with DMF and the concentration can be adjusted to obtain a uniformly dispersed composite conductive slurry B. Continue to perform steps c), d), and e) to obtain a new asymmetric porous conductive film again. In addition, the conductive film conforms to the concept of "green chemistry" advocated by the country, and minimizes environmental pollution through multiple recycling. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 The figure is a scanning electron microscope (SEM) image of the Ag@K2Ti4O9 whisker in the present invention and a flow chart for preparing an asymmetric porous TPU / Ag@K2Ti4O9 conductive film.
[0018] Figure 2 Schematic diagram of the asymmetric porous TPU / Ag@K2Ti4O9 conductive film prepared in the present invention.
[0019] Figure 3 These are the SEM and microscope images of the asymmetric porous conductive film prepared in Example 1.
[0020] Figure 4 These are the SEM and microscope images of the asymmetric porous conductive film prepared in Example 2.
[0021] Figure 5 These are the photograph, SEM image and microscope image of the asymmetric porous conductive film prepared in Example 3.
[0022] Figure 6 The following are photos of the conductive film preparation process in Comparative Example 1, surface microscope images, and comparisons with the SEM images of the cross section of Example 1.
[0023] Figure 7 This is a photo of the preparation process of the conductive film in Comparative Example 2.
[0024] Figure 8 These are photos of the conductive films prepared in Example 2 and Comparative Example 3.
[0025] Fig. 9 These are photos and microscope photos of the conductive film prepared in Comparative Example 4.
[0026] Fig.10 These are photos and microscope photos of the conductive film prepared in Comparative Example 5.
[0027] Fig.11 These are photos and microscope photos of the conductive film prepared in Comparative Example 6.
[0028] Fig.12 The resistance change of the resistor made of the conductive film prepared in Example 1 under different stretching amplitudes.
[0029] Fig.13 The resistance change of the resistor made of the conductive film prepared in Example 1 at different stretching speeds.
[0030] Fig.14 The resistivity variation curve of the resistor made of the conductive film prepared in Example 1 under uniform stretching is shown in FIG.
[0031] Fig.15 The resistance change of the resistor made of the conductive film prepared in Example 1 under a pressure of 1 Pa-1 kPa.
[0032] Fig.16 The resistance change of the resistor made of the conductive film prepared in Example 1 under a pressure of 1 kPa-100 kPa.
[0033] Fig.17 The figure is a summary of the resistance changes of the resistor made of the conductive film prepared in Example 1 under different pressures.
[0034] Fig.18 The resistance change of the resistor made of the conductive film prepared in Example 1 and the non-porous conductive film prepared in Comparative Example 5 under different pressures is compared (a). The resistance change of the non-porous conductive film prepared in Comparative Example 5 under different pressures (b), and the response time of the resistor made of the conductive film prepared in Example 1 (c). DETAILED DESCRIPTION
[0035] The preparation method of the asymmetric porous TPU / Ag@K2Ti4O9 conductive film of the present invention is described in detail below in conjunction with the accompanying drawings, specific embodiments and comparative examples.
[0036] First, prepare the Ag@K2Ti4O9 conductive whiskers used in the implementation:
[0037] 1) Preparation of potassium tetratitanate whiskers
[0038] Add 30g of titanium dioxide with a diameter of 80nm and 17.3g of potassium carbonate into a beaker, and pour in 50ml of distilled water, stir at 60 degrees Celsius until it becomes creamy; bake at 120 degrees Celsius for 3 hours to completely dry it. In a muffle furnace, heat from 800 degrees Celsius to 1000 degrees Celsius at a rate of 1 degree Celsius per minute and keep warm for half an hour. After cooling, boil in distilled water for 2 hours, sieve through a sieve, filter and dry to obtain potassium tetratitanate whiskers for use.
[0039] 2) Potassium tetratitanate coated silver Ag@K2Ti4O9 conductive whiskers.
[0040] The prepared potassium tetratitanate whiskers were dried at 100 degrees Celsius for 30 minutes, then placed in a 50 ml plastic container at room temperature, and then added in a mass ratio of 1:10:5 of potassium tetratitanate whiskers, glucose, and distilled water, and ultrasonicated for 10 minutes to completely dissolve the glucose and disperse the whiskers, and then added with the prepared silver ammonia solution, the amount of silver nitrate added in the silver ammonia solution was five times that of the potassium tetratitanate whiskers, and the reaction system was reacted in an oscillator at a speed of 200 times per second and a temperature of 50 degrees Celsius for 24 hours, and then filtered, washed, and dried to obtain Figure 1 The potassium tetratitanate coated silver Ag@K2Ti4O9 conductive whisker shown has an aspect ratio of about 10-15, a core-shell structure, and the silver element accounts for about 60-90% of the total whisker.
[0041] Example 1
[0042] As Figure 1 The preparation process shown in the figure is as follows: first, thermoplastic polyurethane TPU is mixed with DMF to prepare a solution with a mass concentration of 20%. After complete dissolution, a uniformly dispersed slurry A is obtained. 1 g of Ag@K2Ti4O9 conductive whiskers is added to 5 g of slurry A, stirred for 30 min under dry conditions, and then allowed to stand for 20 min under dry conditions. The slurry is evenly spread on the surface of a glass plate with a diameter of 10 cm, and the spreading amount is 0.3 g / cm 2 , The slurry thickness on the glass plate was about 3 mm. Then it was transferred to an environment with a temperature of 25°C and a relative humidity of 50%RH for 2 h to obtain a pre-cured product C, and the glass plate was immersed in water for 2 h to completely cure it, and the film was peeled off and naturally dried at room temperature to obtain the asymmetric porous TPU / Ag@K2Ti4O9 conductive film of the embodiment of the present invention.
[0043] Example 1 is thicker, such as Figure 3As shown in the electron microscope image, its thickness is about 1 mm, and there are macropores with a diameter of about 0.5 mm on its surface. Due to the presence of this macropore, the resistance of the resistance meter is measured to show that its front resistance is 0.01, which is over the range, and it is considered to be non-conductive, while its bottom resistance is 0.6 Ω, and its conductivity is excellent. At the same time, due to the porous structure on its surface, it has hydrophobic properties. Therefore, this embodiment successfully prepared a thicker asymmetric porous conductive film.
[0044] Example 2
[0045] Thermoplastic polyurethane TPU and DMF were mixed to prepare a solution with a mass concentration of 25%. After complete dissolution, a uniformly dispersed slurry A was obtained. 0.5 g of Ag@K2Ti4O9 conductive whiskers were added to 2 g of slurry A, stirred for 20 min under dry conditions, and then allowed to stand for 10 min under dry conditions. The slurry was evenly spread in a culture dish with a diameter of 10 cm. The thickness of the slurry in the culture dish was about 1.5 mm (the spreading amount was 0.15 g / cm 2 , ). It was transferred to an environment with a temperature of 30°C and a relative humidity of 40%RH for 1 hour to obtain a pre-cured product C, and the culture dish was immersed in water for 2 hours to completely cure it, and the film was peeled off and dried naturally at room temperature to obtain the asymmetric porous TPU / Ag@K2Ti4O9 conductive film of this embodiment.
[0046] like Figure 4 The electron microscope image shown in the figure shows that the thickness is about 0.4 mm and there are small holes with a diameter of about 0.1 mm on the surface. The resistance of the material is measured by a resistance meter and the resistance on the front side is 0.01, which is over the range, and it is considered to be non-conductive, while the resistance on the bottom side is 3.3Ω, which has excellent conductivity. Compared with Example 1, Example 2 is thinner and has a smaller pore size, but it also has an asymmetric porous structure and excellent conductivity.
[0047] Example 3
[0048] Thermoplastic polyurethane TPU and DMF were mixed to prepare a solution with a mass concentration of 15%. After complete dissolution, a uniformly dispersed slurry A was obtained. 0.3 g of Ag@K2Ti4O9 conductive whiskers were added to 2 g of slurry A, stirred for 25 min under dry conditions, and then allowed to stand for 10 min under dry conditions. The slurry was evenly spread in a culture dish with a diameter of 10 cm. The amount of material spread in the culture dish was 0.2 g / cm 2 ,The slurry was spread to a thickness of about 2 mm. The slurry was transferred to an environment with a temperature of 20°C and a relative humidity of 60%RH for 2 h to obtain a pre-cured product C, and the culture dish was immersed in water for 2 h to completely cure it. The film was peeled off and dried naturally at room temperature to obtain the asymmetric porous TPU / Ag@K2Ti4O9 conductive film of this embodiment.
[0049] This embodiment can still form a complete, uniform, large-scale asymmetric conductive film under the above raw material ratio, temperature and humidity conditions. The digital photos, microscope and electron microscope images of the front and back surfaces are as follows: Figure 5 As shown, it also has the characteristics of a porous surface and a relatively smooth back side. Therefore, an asymmetric porous conductive film was also successfully prepared.
[0050] Comparative Example 1
[0051] Thermoplastic polyurethane TPU and DMF were mixed to prepare a solution with a mass concentration of 20%, and a uniformly dispersed slurry A was obtained after complete dissolution. 1g of Ag@K2Ti4O9 conductive whiskers was added to 5g of slurry A, stirred for 30 minutes under dry conditions, and then allowed to stand for 10 minutes under dry conditions, and evenly spread in a culture dish with a diameter of 10cm. The slurry thickness in the culture dish was about 1.5mm. It was transferred to a temperature of 50°C and a relative humidity of 100%RH for 2 hours to obtain a pre-cured product C, and the culture dish was immersed in water for 2 hours to completely cure it, and the film was peeled off and dried naturally at room temperature to obtain Comparative Example 1 of the present invention.
[0052] Comparative Example 1 is a film prepared at a higher temperature, such as Figure 6 The microscope image and electron microscope image shown in the figure do not have a cuticle layer, that is, they do not have an asymmetric structure. Figure 6 The cross-sectional electron microscope image shows that the bonding mode between the whiskers and TPU is completely different from that of Examples 1-3, which is due to the inability of TPU to anchor the whiskers at high temperatures. Therefore, Comparative Example 1 is a failure example, and an asymmetric film cannot be prepared.
[0053] Comparative Example 2
[0054] Thermoplastic polyurethane TPU and DMF were mixed to prepare a solution with a mass concentration of 10%, and a uniformly dispersed slurry A was obtained after complete dissolution. 0.2g of Ag@K2Ti4O9 conductive whiskers were added to 2g of slurry A, stirred for 30 min under dry conditions, and then allowed to stand for 10min under dry conditions, and evenly spread in a culture dish with a diameter of 10cm. The slurry thickness in the culture dish was about 1.5mm. It was transferred to a temperature of 25°C and a relative humidity of 50%RH for 2 hours to obtain a pre-cured product C, and the culture dish was immersed in water for 2 hours to completely cure it, and the film was peeled off and dried naturally at room temperature to obtain Comparative Example 2 of the present invention.
[0055] The concentration and quality of TPU and whiskers in the slurry in Comparative Example 2 are both low. Figure 7 In the petri dish and film images shown, during the non-solvent induced phase separation process, a large amount of water was absorbed by DMF and TPU precipitated slowly, so the precipitated TPU could not fix the whisker network structure well, thus making the surface uneven. Therefore, Comparative Example 2 is a failure example.
[0056] Comparative Example 3
[0057] Thermoplastic polyurethane TPU and DMF were mixed to prepare a solution with a mass concentration of 20%, and a uniformly dispersed slurry A was obtained after complete dissolution. 1g of Ag@K2Ti4O9 conductive whiskers was added to 5g of slurry A, stirred for 30 min under dry conditions, and then allowed to stand for 10min under dry conditions, and evenly spread in a culture dish with a diameter of 10cm. The slurry thickness in the culture dish was about 1.5mm. It was transferred to a temperature of 20℃ and a relative humidity of 10%RH for 6 hours to obtain a pre-cured product C, and the culture dish was immersed in water for 2 hours to completely cure it, and the film was peeled off and dried naturally at room temperature to obtain Comparative Example 3 of the present invention.
[0058] Comparative Example 3 was prepared under a relatively low humidity, and therefore required 6 hours to be completely cured. Even if the curing time was longer, the film surface was uneven due to the inappropriate temperature and humidity, such as Figure 8 As shown, compared with Example 2, the film quality is poor, so this comparative example 3 is also a failure example, that is, when the humidity is lower than a certain range, it is impossible to prepare an asymmetric film of qualified quality.
[0059] Comparative Example 4
[0060] Thermoplastic polyurethane TPU and DMF were mixed to prepare a solution with a mass concentration of 20%, and a uniformly dispersed slurry A was obtained after complete dissolution. 1 g of Ag@K2Ti4O9 conductive whisker was added to 5 g of slurry A, and the mixture was stirred for 30 min under dry conditions, and then allowed to stand for 10 min under dry conditions, and evenly spread in a culture dish with a diameter of 10 cm. The thickness of the slurry in the culture dish was about 1.5 mm; then it was transferred to an environment with a temperature of 10°C and a relative humidity of 50%RH for 2 h to obtain a pre-cured product C, and the culture dish was immersed in water for 2 h to fully cure it, and the film was peeled off and dried naturally at room temperature to obtain Comparative Example 4 of the present invention.
[0061] like Fig. 9 As shown, this comparative example was prepared at a lower temperature. Since the viscosity of the slurry changes at a lower temperature, the prepared film is not very uniform and is relatively hard, and almost no holes can be seen on the surface. Therefore, this comparative example is also a failure example, that is, when the temperature is lower than a certain range, the concentration of the slurry changes, and an asymmetric film of qualified quality cannot be prepared.
[0062] Comparative Example 5
[0063] Thermoplastic polyurethane TPU and DMF were mixed to prepare a solution with a mass concentration of 20%. After complete dissolution, a uniformly dispersed slurry A was obtained. 1g of Ag@K2Ti4O9 conductive whiskers was added to 5g of slurry A, stirred for 30 minutes under dry conditions, and then allowed to stand for 10 minutes under dry conditions, and evenly spread in a culture dish with a diameter of 10cm. The thickness of the slurry in the culture dish was about 1.5 mm. It was transferred to an environment with a temperature of 80°C and a relative humidity of 50%RH for 30 minutes to obtain a pre-cured product C, and the culture dish was immersed in water for 2 hours to completely cure it. The film was peeled off and dried naturally at room temperature to obtain the film of this comparative example, as shown in FIG. Fig.10 .
[0064] Depend on Fig.10 It is judged that the comparative example has a high temperature, which causes a large amount of DMF to volatilize during the molding process, so the preparation molding speed is fast, and it can be completely molded in only 30 minutes. At the same time, due to the volatilization of DMF, the film compactness increases (no longer has a porous structure) and the film becomes thinner, and the performance in the pressure-sensitive test is poor. Therefore, this comparative example is a failed example.
[0065] Comparative Example 6
[0066] Thermoplastic polyurethane TPU and DMF were mixed to prepare a solution with a mass concentration of 20%. After complete dissolution, a uniformly dispersed slurry A was obtained. 1g of Ag@K2Ti4O9 conductive whiskers was added to 5g of slurry A, stirred for 30 minutes under dry conditions, and then allowed to stand for 10 minutes under dry conditions, and evenly spread in a culture dish with a diameter of 10cm. The thickness of the slurry in the culture dish was about 1.5 mm. It was transferred to an oven at 120°C (in the oven, the relative humidity was considered to be 0%RH) and left for 20 minutes. After complete curing, the film could be peeled off to obtain the film of this comparative example 5. Fig.11 shown.
[0067] Depend on Fig.11 It can be judged that this comparative example uses the commonly used "drying" molding method. It can be observed from the pictures that the composite film of silver-coated potassium tetratitanate whiskers and TPU prepared by this method not only has no holes, but is also extremely rough with pits and pits, and has no pressure-sensitive properties at all.
[0068] Through the comparison results of the implementation of the above comparative examples, it can be seen that the method of preparing the thin film by non-solvent induced phase separation in the air at a preferred certain humidity and temperature in each embodiment of the present invention has a simple preparation process and can prepare an asymmetric surface porous composite membrane in one step, which has great superiority and pressure sensitivity.
[0069] In order to verify the tensile and pressure-sensitive properties of the film prepared by the present invention, a 2 cm×0.5 cm resistor sheet was prepared by taking the TPU / Ag@K2Ti4O9 asymmetric conductive film of Example 1 as an example, and its pressure performance and resistance response performance were tested. The results are as follows: Figure 12-18 As shown in Figure 2, different strains (2.5-12.5%) and stretching speeds (1.0-20 mm·min -1 The dynamic transient resistance response under Fig.12 and Fig.13 The tensile resistance change of TPU / Ag@K2Ti4O9 film ((R0-R) / R) is shown in Fig.14 .exist Fig.15 and Fig.16 The resistance changes of TPU / Ag@K2Ti4O9 films at different pressures are compared and summarized in Fig.17 middle. Fig.18 a is a comparison of the resistance changes of the porous membrane (left) and the non-porous membrane (right) under different pressures. Fig.18 b is the resistance change of the non-porous TPU / Ag@K2Ti4O9 film. Fig.18 c Response / recovery time of asymmetric porous TPU / Ag@K2Ti4O9 conductive film.
[0070] By measuring the relative resistance change of the above-mentioned conductive film resistor under different mechanical stimuli, the sensing performance of the asymmetric porous TPU / Ag@K2Ti4O9 conductive film was verified. Fig.12 The figure shows the resistance change curve of the asymmetric porous TPU / Ag@K2Ti4O9 conductive film under different tensile strains. Under different tensile amplitudes, the resistance of the TPU / Ag@K2Ti4O9 conductive film increases accordingly with the increase of tensile strain, which indicates that the asymmetric porous TPU / Ag@K2Ti4O9 conductive film can be used as a tensile strain sensor to quantitatively analyze the amplitude of the applied tensile strain. Fig.13 It can be seen that the resistance of the film does not change much under different stretching speeds, which means that the film can work stably at different movement speeds. Fig.14 It can be seen that with stretching, ΔR / R0 increases, and ΔR / R0 and tensile strain can be well fitted in an exponential form (R 2 >0.9999), and the sensible strain range is 0-50%. Figure 15-17 The comparison of the real-time resistance response of the asymmetric porous TPU / Ag@K2Ti4O9 conductive film under different pressures of 1 Pa ~100 kPa is shown. The TPU / Ag@K2Ti4O9 conductive film can even detect the input signal at about 5 Pa ( Fig.15 , indicating that its detection limit is about 5 Pa. In addition, the conductive film exhibits a larger relative resistance change in the higher pressure region (1-100 kPa) ( Fig.16 ), which shows that it can not only detect smaller pressures but also work stably under high pressures. Fig.17 The resistance changes under different pressures are summarized. As a control sample, the resistance change of the non-porous TPU / Ag@K2Ti4O9 film prepared under drying conditions at 80°C in Comparative Example 5 was also tested ( Fig.18 b). It is obvious that the non-porous TPU / Ag@K2Ti4O9 hybrid membrane does not work well at high pressure and has poor reproducibility. Fig.18 a is a comparison of the resistance changes of the porous membrane of Example 1 and the non-porous membrane of Comparative Example 5 under different pressures, which further illustrates the key role of the porous structure.
[0071] The asymmetric porous TPU / Ag@K2Ti4O9 hybrid membrane can also monitor ultrafast pressure signals with a very short response time of 125 ms, which can meet most daily applications ( Fig.18 c).
Claims
1. A method for preparing an asymmetric porous TPU / Ag@K2Ti4O9 conductive film, characterized in that: The steps include: a) mixing thermoplastic polyurethane (TPU) and N, N-dimethylformamide (DMF) to prepare a mixed solution with a mass concentration of 15-25%, and obtaining a uniformly dispersed slurry A after the mixture is completely dissolved; b) First, Then, Ag@K2Ti4O9 conductive whiskers with a mass of 15-25% of the total mass of slurry A in step a) are added to slurry A, stirred for 20-40 min under dry conditions, and then allowed to stand for 10-20 min under dry conditions to obtain a uniformly dispersed conductive slurry B, wherein the mass ratio of TPU to Ag@K2Ti4O9 conductive whiskers in the slurry B is 1:1; the conductive whiskers are core-shell Ag@K2Ti4O9, and the mass ratio of silver atoms wrapped in the conductive whiskers is 60-90%; in this step, the preparation method of Ag@K2Ti4O9 conductive whiskers is as follows: potassium tetratitanate whiskers with an aspect ratio of 10-15 are dried at 100°C for 30-60 min, and then glucose and distilled water are added at room temperature, wherein the mass ratio of potassium tetratitanate, glucose and distilled water is 1:6-10:3-5, and after mixing, ultrasonically heated at room temperature for 10-20 min. min until glucose is completely dissolved and whiskers are completely dispersed, then silver ammonia solution is added, and the reaction is carried out in an oscillator at a speed of 200 times / second at 40-50°C for 24-30 hours, and then filtered, washed and dried to obtain Ag@K2Ti4O9 conductive whiskers; c) Precured film: evenly spread the conductive paste B in step b) on the surface of the glass plate, let it stand for defoaming in a dry environment for 10 to 20 minutes, and then transfer it to an environment with a temperature of 20 to 30 °C and a relative humidity of 40 to 60% RH for 1 to 3 hours to obtain a precured product C; d) immersing the pre-cured product C in step c) together with the glass plate in water for 1 to 3 hours to completely cure it, and peeling off the film to obtain a cured film D; e) The film cured in step d) is naturally dried at room temperature to obtain a porous PU / Ag@K2Ti4O9 conductive film.
2. The method for preparing a symmetrical porous PU / Ag@K2Ti4O9 conductive film according to claim 1, characterized in that: In step c), the conductive paste B is applied on the glass plate at a rate of 0.1 to 0.3 g / cm 2 .
Citation Information
Patent Citations
Method for preparing porous meta-aramid diaphragm through non-solvent induced phase separation method
CN113381122A
Antioxidant low-sheet-resistance transparent conductive film
CN113838598A
Flexible transparent conductive film and preparation method thereof
CN113871054A
Conductive film and manufacturing method thereof
CN113889295A